IMAGING FINDINGS ON CHEST X-RAY IN PATIENTS WITH COVID-19 - Jakimovska, Maja; Stojovska Jovanovska, Elizabeta; Spirov, Vasilco; Stojkoski, Aleksandar; Janevski, Petar; Ilievski, Mirko (Journal of Morphological Sciences; Vol 3 No 2 (2020): JMS, 2020)
Purpose: To describe the most common manifestations and patterns of parenchymal abnormalities in patients with confirmed corona virus disease. Methods: Chest X -ray is the first imaging method to diagnose COVID 19 corona virus infection because it is cheap, readily available and can easily be cleaned. Portable radiography units are preferred. We retrospectively reviewed the chest x-rays in hospitalized patients for COVID-19. Radiologists can recognize and identify pulmonary involvement, airspace opacities, consolidation, ground-glass opacity, pulmonary lesion distribution, lobe predomination and unlike parenchymal abnormalities. Results: The main symptom in our patients was fever. The most frequent findings on X-ray were airspace opacities, whether described as consolidation or ground glass opacity. The distribution was most often bilateral, peripheral and lower zone predominant. No patient presented cavitations. Conclusion: Chest X- ray is effective, fast and useful tool to diagnose COVID 19 and it is a first line diagnostic imaging tool. Keywords : COVID-19, corona virus infection, chest X-ray, pneumonia, ground glass opacity.